2020
DOI: 10.1038/s41598-020-65593-x
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of flame retardant, PBB153, exposure on sperm and future generations

Abstract: In 1973, the Velsicol Chemical Company, which manufactured FireMaster, a brominated flame retardant, and NutriMaster, a nutritional supplement, mistakenly shipped hundreds of pounds of FireMaster to grain mills around Michigan where it was incorporated into animal feed and then into the food chain across the state. An estimated 6.5 million Michigan residents consumed polybrominated biphenyl (PBB)-laced animal products leading to one of the largest agricultural accidents in U.S. history. To date, there have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This work has since been independently replicated (15), highlighting the reproducibility of our methodology. To first determine whether nhpESCs differentiate into spermatogenic cells similar to hESCs and hiPSCs, we differentiated nhpESCs in mouse SSC culture conditions as previously described (10,15,30,(32)(33)(34)(35)(36). We chose nhpESC H2B-GFP line for downstream analyses, but all lines tested (Supplemental Fig.…”
Section: Results Nhpescs Can Be Differentiated Into Spermatogenic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work has since been independently replicated (15), highlighting the reproducibility of our methodology. To first determine whether nhpESCs differentiate into spermatogenic cells similar to hESCs and hiPSCs, we differentiated nhpESCs in mouse SSC culture conditions as previously described (10,15,30,(32)(33)(34)(35)(36). We chose nhpESC H2B-GFP line for downstream analyses, but all lines tested (Supplemental Fig.…”
Section: Results Nhpescs Can Be Differentiated Into Spermatogenic Cellsmentioning
confidence: 99%
“…Genomic DNA from diploid nhpESCs and haploid cells obtained from FACS was isolated using the DNeasy Blood and Tissue kit from Qiagen following the manufacturer’s instructions. Samples were prepared for imprint control region methylation analyses as previously described ( 30 ) with the EpiTect Methyl DNA Restriction Kit (Qiagen) as per the manufacturer’s instructions. For quantitative polymerase chain reaction (qPCR)-based analyses of imprint control region methylation for H19 and SNRPN for each sample, the following EpiTect qPCR Methyl Promoter Primers were used: H19 , catalog number 335002 EPHS102101–1A, and SNRPN , 335002 EPHS104389–1A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None the less, some evidence in humans does exist. For example, paternal toxicant exposures and even endurance training have been shown to result in altered ncRNA content of spermatozoa and methylation [110,[115][116][117][118][119]. Involvement of epigenetic mechanisms transferred from father to offspring was suggested by Knudsen et al based on a preliminary EWAS analyses of 195 Bergen RHINESSA and ECRHS participants, showing that father's smoking was associated with specific DNA methylation patterns in adult offspring [120].…”
Section: Mechanisms Behind Transmission Of Exposure Effects From Parents To Offspringmentioning
confidence: 99%
“…Greeson et al examined environmental exposure to PBB153, a polybrominated biphenyl compound used as a flame retardant that accidentally entered the food chain in 1973, and led to alterations in liver and thyroid functions, as well as to increased odds of lymphomas and cancers of the digestive tract. The authors demonstrated that higher serum PBB153 levels were associated with decreased methylation of imprint control regions, which in turn demonstrated that this contaminant determines alterations to the germ line which are then potentially transferred to the offspring of these men 13 . Other environmental effects, such as diets, are more difficult to measure.…”
mentioning
confidence: 99%